Active Bridge Rectifier With DM EMI Reduction Based on Linear Reverse Operation of MOSFETs - Wang, Ke-Wei; Zhang, Kun; Tung, Chung-Pui; Chung, Henry Shu-Hung (IEEE transactions on power electronics, 2021)
A new linear control scheme for operating power MOSFETs in the third quadrant (i.e., synchronous rectifier (SR) operation) is proposed and applied to electromagnetic interference (EMI) mitigation of switching converters. MOSFETs operating in the third quadrant exhibit electrical characteristics equivalent to a voltage-controlled voltage source between the gate-source and the drain-source voltages. Such operation is an alternative to typical SR mode, allowing fast control of the ac drain-source voltage. It is applied to active bridge rectifiers (ABRs) that can produce the necessary high-frequency voltage compensation signal to reduce differential-mode EMI. The ABR can then play the role of ac line rectification and EMI reduction at the same time. Its characteristics are modeled, and experimental verifications are carried out on a boost-type power factor corrector (PFC). The EMI performance of the PFC is improved with the proposed technique. The proposed technique facilitates the reduction of passive filter size and gives the potential of integrating active filtering function into the ABR as a solid-state front-end module. The idea can, thus, help increase the power density of power converters.